2017
DOI: 10.3389/fneur.2017.00646
|View full text |Cite|
|
Sign up to set email alerts
|

Sliding Mode Tracking Control of a Wire-Driven Upper-Limb Rehabilitation Robot with Nonlinear Disturbance Observer

Abstract: Robot-aided rehabilitation has become an important technology to restore and reinforce motor functions of patients with extremity impairment, whereas it can be extremely challenging to achieve satisfactory tracking performance due to uncertainties and disturbances during rehabilitation training. In this paper, a wire-driven rehabilitation robot that can work over a three-dimensional space is designed for upper-limb rehabilitation, and sliding mode control with nonlinear disturbance observer is designed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The position tracking of the end-effector is realized through the PID controller, and the PID controller parameters can be adjusted by the fuzzy algorithm according to the change of cable tensions to ensure the safety of the patient [20]. In addition, the robust adaptive control method [26], sliding mode control method [27]- [28], and force-position control method [29] were studied to realize position tracking control of the robot.…”
Section: Dofs Lle (Lower Limb Exoskeletonmentioning
confidence: 99%
“…The position tracking of the end-effector is realized through the PID controller, and the PID controller parameters can be adjusted by the fuzzy algorithm according to the change of cable tensions to ensure the safety of the patient [20]. In addition, the robust adaptive control method [26], sliding mode control method [27]- [28], and force-position control method [29] were studied to realize position tracking control of the robot.…”
Section: Dofs Lle (Lower Limb Exoskeletonmentioning
confidence: 99%
“…The CDRR used in this study was reported previously [35], but was upgraded from three cables to redundant four cabledriven robot (Fig. 1).…”
Section: A Kinematics Of Cdrrmentioning
confidence: 99%
“…Let . When the disturbance varies slowly relative to the observer dynamics, which is commonly assumed in observer design [ 48 , 49 ], it is reasonable that , so we have …”
Section: Control Strategymentioning
confidence: 99%